2019
DOI: 10.1177/1093526619836025
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Distinct Immunohistochemical Distribution of Annexin A5, C3b, C4d, and C5b-9 in Placentas From Patients With Antiphospholipid Antibodies, Preeclampsia, and Systemic Lupus Erythematosus

Abstract: Introduction In pregnancy, the presence of preeclampsia (PEC), systemic lupus erythematosus (SLE), and/or antiphospholipid antibody syndrome (APLS) is characterized by poor obstetric outcomes, with potential adverse effects for both mother and fetus. Although the histopathologic changes observed in these entities have been well established, the pathogenic mediators associated with tissue injury are poorly understood. Methods Forty placentas were evaluated, including 10 patients with preeclampsia, 9 with SLE, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In the PROMISSE cohort, these markers of C activation (Bb and SC5b-9) were detected in the circulation in early gestation among those SLE/aPL + women who later developed pregnancy complications (53). Analysis of placentae from aPL-negative SLE patients by Matrai and colleagues revealed signs of tissue malperfusion, infarction and intervillous thrombi and increased deposits of C4d and C5b-9 on syncytiotrophoblasts and extravillous trophoblasts compared to controls (56). The extent of C4d deposition was found to be inversely correlated with low placental and birth weight (91).…”
Section: Complement and Systemic Lupus Erythematosus In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…In the PROMISSE cohort, these markers of C activation (Bb and SC5b-9) were detected in the circulation in early gestation among those SLE/aPL + women who later developed pregnancy complications (53). Analysis of placentae from aPL-negative SLE patients by Matrai and colleagues revealed signs of tissue malperfusion, infarction and intervillous thrombi and increased deposits of C4d and C5b-9 on syncytiotrophoblasts and extravillous trophoblasts compared to controls (56). The extent of C4d deposition was found to be inversely correlated with low placental and birth weight (91).…”
Section: Complement and Systemic Lupus Erythematosus In Pregnancymentioning
confidence: 99%
“…More convincing evidence supporting the role of C in inducing aPLdependent placental damage and pregnancy failure has been obtained from the immunohistochemical analysis of placental tissue for C deposits. The presence of C4d in placentae from APS women has been documented at the fetal-maternal interface, in particular on syncytiotrophoblast basement membrane, and to some extent also on extravillous trophoblasts of the basal plate by three groups (55)(56)(57). C4 deposits were found to be associated with intrauterine fetal death (55) and placental abnormalities including decidual vasculopathy, increased syncytial knots, and villous infarcts (57).…”
Section: Complement and Obstetric Anti-phospholipid Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…If animal models have clearly shown that activation of complement is required to produce aPL-mediated pregnancy loss and inflammation and complement deposition at trophoblast and placental level was described [10], histopathological data from human disease are not consistent. In fact, human placenta analysis does not unanimously show complement deposition, and inflammation (chorioamnionitisis or villitis) does not seem always associated with aPL-mediated pregnancy loss [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation final product, membrane attack complex (MAC,, can form on the cell and directly cause the chondrocyte death by osmotic flux (Heinen et al, 2009). Also, MAC can promote the production of matrix metalloproteinases (MMPs) and cyclooxygenase which induces the formation of OA (Matrai et al, 2019). Therefore, how to block the complement activation, especially MAC, will become a potential strategy for OA treatment (Evans, 2005;Fortier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%